If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -54 = 14 Reorder the terms: -54 + -4x = 14 Solving -54 + -4x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '54' to each side of the equation. -54 + 54 + -4x = 14 + 54 Combine like terms: -54 + 54 = 0 0 + -4x = 14 + 54 -4x = 14 + 54 Combine like terms: 14 + 54 = 68 -4x = 68 Divide each side by '-4'. x = -17 Simplifying x = -17
| 3(x-2)=3x+15 | | 5.3(4+2x)-9.2=12 | | 8x-5=-109 | | 28n^3-35n^2+32n-40=0 | | y+-7+y=2y+-7 | | 6x^2+7-3=0 | | 8m^2+6m-9=0 | | 10-2y=8 | | 725.00+10.50x=19.50x | | s+s+s-2=3s+7 | | 19.50x=2500 | | 49b^3-9b=0 | | 8x^2+26x=0 | | s+s+s-2=3s | | -8x^2-11=-43 | | 40y-19=1381 | | -8x^2-11=43 | | 725.00+10.50x=2500 | | 39x+44=543 | | 4-d=-1(d-4) | | 25Y+5=180 | | 14x^2+21x=0 | | 6x=2+24 | | 3a-4b=5 | | -14x-7=77 | | -3+.50x=.2x+x-.55+.625 | | 14Y+4=11Y+1 | | 5x+8y=8x | | 18x^2-15x=0 | | 2x-3+4x=6x+11 | | -2(9-3s)-(5s+2)=-25 | | -4x+8=4 |